The Effect of Using the ChatGPT Application on Students' Analytical Abilities - Siahaan, Rina Devi; Novita, Herlina; Simanungkalit, Rick Hunter; Marpaung, Rince; Napitupulu, Rio Parsaoran; Saragih, Sepriandison (Universitas Wiralodra, 2025)
The rapid development of artificial intelligence (AI) has significantly influenced various aspects of human life, including the field of education. One of the most widely used AI tools today is ChatGPT, a language model developed by OpenAI. This application can respond to questions, generate essays, explain complex concepts, and assist students in completing academic tasks in a clear and interactive manner.This study aims to examine the effect of using the ChatGPT application on the analytical skills of students at HKBP Nommensen University, Pematangsiantar. ChatGPT is a natural language-based artificial intelligence model that is now starting to be used as a learning companion in various fields of science, including higher education. This study used a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The sample consisted of 60 students, divided into two groups: experimental and control. The research instrument was a descriptive test of analytical skills that had been validated by experts. The results of data analysis using ANCOVA showed a significant effect of the use of ChatGPT on students' analytical skills (p < 0.05). These findings indicate that ChatGPT can contribute positively to the development of students' analytical thinking skills if used appropriately and directed in learning.